2001
DOI: 10.1143/jjap.40.l592
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Absorption Spectra of C Local Mode in Si1-x-yGexCy Crystals

Abstract: The local vibration mode of substitutional C atoms (C-LVM) in high-quality Si1-x-y Ge x C y crystals was studied by infrared absorption spectroscopy. The peak intensity and full width at half maximum of C-LVM were found to change depending on Ge content as well as substitutional C content. However, the integrated intensity of C-LVM exhibited a linear dependence on the substitutional C content. These results demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…10,11) The other issue is that C atoms are incorporated not only in the substitutional but also in the interstitial sites because of its relatively low solubility in SiGe. [12][13][14][15] Until now, SiGe:C are grown on Si(001) using molecular beam epitaxy (MBE), [16][17][18][19] and chemical vapor deposition (CVD) [10][11][12]14) method, and analyzed the amount of interstitial and substitutional C. In CVD, the precursors for C are SiH 3 CH 3 , [10][11][12]14) or C 2 H 4 . 20) Substitutional C concentration was characterized by other method as infrared absorption spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11) The other issue is that C atoms are incorporated not only in the substitutional but also in the interstitial sites because of its relatively low solubility in SiGe. [12][13][14][15] Until now, SiGe:C are grown on Si(001) using molecular beam epitaxy (MBE), [16][17][18][19] and chemical vapor deposition (CVD) [10][11][12]14) method, and analyzed the amount of interstitial and substitutional C. In CVD, the precursors for C are SiH 3 CH 3 , [10][11][12]14) or C 2 H 4 . 20) Substitutional C concentration was characterized by other method as infrared absorption spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…20) Substitutional C concentration was characterized by other method as infrared absorption spectroscopy. 13) References 19, 21, and 22 reported that a number of Ge-C bonds in SiGe:C would be very small or not formation by Raman spectroscopy or Monte Carlo studies. As described above, sites of C have be interested and researched.…”
Section: Introductionmentioning
confidence: 99%